2021
DOI: 10.1177/14680874211008005
|View full text |Cite
|
Sign up to set email alerts
|

Development of common rail lube oil injector for large two-stroke marine diesel engines

Abstract: The two-stroke crosshead diesel engines, nowadays moving the majority of merchant vessels, have lubrication systems which significantly contribute to their overall emissions, since they work on total loss basis: a relevant fraction of lubricant enters the exhaust duct, increasing total exhaust emissions. This paper demonstrates that a viable solution to reduce lubrication system related emissions can be found in the application of a new common rail type ( CR) lubrication system. Particularly, in the first part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In the 2-stroke marine diesel engines, lubricant is injected into the liner wall, the injected lubricant is no longer recycled, to reduce oil consumption and its harmful emissions, the control of oil injection quantity is very strict. 9 So, the PRCL system suffers starved lubrication. Especially for the top ring, some relevant experimental studies have also verified its starved lubrication state.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2-stroke marine diesel engines, lubricant is injected into the liner wall, the injected lubricant is no longer recycled, to reduce oil consumption and its harmful emissions, the control of oil injection quantity is very strict. 9 So, the PRCL system suffers starved lubrication. Especially for the top ring, some relevant experimental studies have also verified its starved lubrication state.…”
Section: Introductionmentioning
confidence: 99%
“…They found that for lower pressure in the rail, reducing the dwell time between the first and second pulses resulted in a faster start of injection for the second event. While the experimental techniques outlined were developed for and have almost exclusively been used to study fuel injectors, some authors have also looked at lubrication oil injectors using a simulation approach [61,62]. Stark et al [61] simulated the hydraulic characteristics of a lubrication oil injector using the 1D LubeFluid code.…”
Section: Internal Nozzle Dynamicsmentioning
confidence: 99%
“…The injector was simulated at an injection pressure of 900 bar, which is a very large injection pressure for a lubrication oil injector. Milanese et al [62] also simulated the hydraulic response of a lubrication oil injector. They used a software called AMESim to simulate the injector.…”
Section: Internal Nozzle Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations